2016
DOI: 10.1002/hyp.11032
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling complex hydrogeological processes in Andean basins in south‐central Chile: An integrated assessment to understand hydrological dissimilarity

Abstract: Groundwater storage, drainage, and interbasin water exchange are common hydrological processes but often difficult to quantify due to a lack of local observations. We present a study of three volcanic mountainous watersheds located in south‐central Chile (~36.9 ° S) in the Chillán volcanic complex (Chillán, Renegado, and Diguillín river basins). These are neighboring basins that are similar with respect to the metrics normally available for characterization everywhere (e.g., precipitation, temperature, and lan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 37 publications
1
29
0
Order By: Relevance
“…The water balance was analyzed through a conceptual model approach to better understand the hydrologic behavior of the Renegado and Alto Diguillín watersheds [12]. The model simulates the rainfall-runoff and snowmelt-runoff processes.…”
Section: Water Balance Analysismentioning
confidence: 99%
See 3 more Smart Citations
“…The water balance was analyzed through a conceptual model approach to better understand the hydrologic behavior of the Renegado and Alto Diguillín watersheds [12]. The model simulates the rainfall-runoff and snowmelt-runoff processes.…”
Section: Water Balance Analysismentioning
confidence: 99%
“…The model needs the rainfall and the potential evapotranspiration as inputs, and the output is the total runoff at the watershed outlet, including both subterraneous and direct runoff, the amounts of which are calculated through six calibration parameters, plus two for the input modification (useful in the case of non-representative PM and PET data). Further description about the model, its implementation, and calibration can be found in [12].…”
Section: Water Balance Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Meanwhile, conceptual models have the advantage of requiring a lower quantity of input data (e.g., precipitation, temperature), but generate a simplified representation of the physical processes that occur in a watershed. Nonetheless, various recent investigations have shown that conceptual models can provide reliable models (e.g., Skaugen et al [6]; Toledo et al [7]; Muñoz et al [8]; Parra et al [9]); therefore, a conceptual model is a reliable alternative for studying hydrological processes in watersheds with limited hydrological information.…”
Section: Introductionmentioning
confidence: 99%